General practice consultation patterns by teenagers and their associations with health risks, needs and attitudes - Churchill, Richard (2008)
During the transition from childhood to adulthood young people are vulnerable to relatively unique health problems and risks, whilst also developing personal autonomy, and learning when and how to access health services. This thesis describes three studies, the overall aim of which was to gain a greater understanding of how teenagers use general practice, and to identify those factors that influence this behaviour and ultimate health outcomes.